2020
DOI: 10.1021/acscatal.0c02799
|View full text |Cite
|
Sign up to set email alerts
|

Propene Production by Butene Cracking. Descriptors for Zeolite Catalysts

Abstract: Among the possible on-purpose technologies for propene production, direct conversion of butene-rich fractions to propene represents an attractive alternative to conventional routes such as steam cracking or fluid catalytic cracking (FCC). Here we present an approach for designing an efficient ZSM-5 based catalyst for the selective cracking of butenes to propene by properly balancing diffusional and compositional effects. Instead of the large coffin-shaped ZSM-5 crystallites with very high Si/Al ratios generall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 77 publications
0
25
0
Order By: Relevance
“…[37][38][39] Within the olefin cycle of the HCP, olefins convert methanol to olefins autocatalytically, where olefins are repeatedly methylated to higher olefins that are subsequently cracked to lighter olefins. 28,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] In the dual cycle concept (see Scheme 1) aromatic species also play a role in the production of light olefins, and ethene and propene in particular. 6,[8][9][10][11][12][13][14]30 This is highly interesting both from a conceptual but also practical point of view, as the selectivity towards lighter olefins might significantly differ for these two cycles.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] Within the olefin cycle of the HCP, olefins convert methanol to olefins autocatalytically, where olefins are repeatedly methylated to higher olefins that are subsequently cracked to lighter olefins. 28,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] In the dual cycle concept (see Scheme 1) aromatic species also play a role in the production of light olefins, and ethene and propene in particular. 6,[8][9][10][11][12][13][14]30 This is highly interesting both from a conceptual but also practical point of view, as the selectivity towards lighter olefins might significantly differ for these two cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, differentiating diffusivities in straight and sinusoidal channels for these anisotropic molecules over H-ZSM-5 zeolites are benefit to the understanding of activity, stability or product distribution in catalysis and the guidance of catalyst design with designated morphology. The catalytic cracking of low-value C4+ olefins fractions (OCC), deriving from fluid catalytic cracking (FCC) and methanol to olefins (MTO) processes 7,[20][21][22] , represents a meaningful route to improve the ethylene and propylene production (important to the polymer industry) using H-ZSM-5 catalysts in industrial application [23][24][25][26][27] . Herein, the olefin catalytic cracking process was employed to clarify the descriptor of morphology effect in catalysis process by revealing the diffusion anisotropy in straight and sinusoidal channels of H-ZSM-5 zeolite.…”
Section: Schame 1 Amentioning
confidence: 99%
“…It was reported that regulating the preferred orientations of the pore systems to crystal planes will cause the variety of the H-ZSM-5 morphologies, thus correspondingly affecting the diffusion resistances 5,6 . Morphology adjustment by reducing the particle size and shape with a controllable a/b or a/c "aspect ratios" is considered as an efficient route to reduce the diffusion path lengths, increase the accessibility of active sites, and finally promote catalytic activities of H-ZSM-5 samples [7][8][9][10][11][12] . In particular, constructing H-ZSM-5 catalysts with intergrowths on well-defined crystal facet opening 7,12 or nanosheet morphology with extremely short thickness along b-axis 8,9,11 , showing remarkably longer lifetime in catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrocarbon catalytic cracking is a traditional topic that has been researched for almost a century. Detailed information about hydrocarbon behavior over zeolites is of significant importance to the production of light olefins, [1][2][3][4][5] the petroleum process, [6][7][8] solid waste resources, [9][10][11][12] etc.…”
Section: Introductionmentioning
confidence: 99%